Occurrence of infectious endocarditis in intravenous drug users (Research, Society and Development, 2021)
The general objective of this article is mainly to alert about the risk of occurrence of Infectious Endocarditis not only in the elderly or in patients with cardiovascular pathologies, but also in young and previously healthy people who are exposed to the causative agents of this infection through the use of intravenous drugs due to sharing contaminated needles. To obtain the results and answers about the problematization presented in this work, an explanatory research was carried out using the bibliographic analysis of review articles published between 2008 and 2019 on the Scielo and Google academic platforms. one of the articles. Endocarditis in general refers to infection of the cardiac endocardial tissue. A heart without existing pathological conditions is somewhat resistant to this infection, as the constant blood flow makes it difficult for these microorganisms to adhere to this tissue. Therefore, the main causes of this condition are congenital endocardial abnormalities, presence of pathogenic microorganisms in the bloodstream, calcified or bicuspid aortic valves, rheumatic valve disease, mitral valve prolapse and hypertrophic cardiomyopathy and previous endocarditis. As prophylaxis, dental evaluation and medication are essential before surgery to repair congenital heart disease or valves. However, it is essential not to use intravenous drugs and share needles, as this can lead to endocarditis in people who were healthy until then and who do not have heart problems before the episode.